Desenvolvimento de material compósito a base de raspa de pneu e látex para isolamento térmico - Ford, Elmo Thiago Lins Couras (2011)
The process of recycling has been stimulated by the markets for several reasons, mainly on economical and environmental. Several products have been developed from recycled materials that already exist as well as several residues have been studied in different forms of applications. The greater majority of the applications for thermal insulation in the domestic, commercial and industrial systems have been elaborated in the temperature ranges between low to medium reaching up to 180oC. Many materials such as glass wool, rock wool, polystyrene are being used which are aggressive to the environment. Such materials in spite of the effectiveness in the retention of heat flow, they cost more and when discarded take several years to be absorbed by the nature. This way, in order to adapt to a world politics concerning the preservation of the environment, the present study was intended to develop a material composed of natural/biodegradable materials and industrial residues. The development of such a product in the form of a composite material based on tyre scrapes and latex for thermal insulation is presented in this research work. Thermal and physical properties of the tire scrapes as well as latex were studied in order to use them as raw materials for the manufacture of the intended composite to be applied as a thermal insulator in hot and cold systems varying between 0ºC and 200oC, respectively. Composite blankets were manufactured manually, in weight proportions of 1:1 (50:50%); 1:2 (33:67%) and 2:1 (67:33%) (tire scrapes: latex) respectively. Physical, mechanical and thermal properties of the composites were analyzed to obtain data about the viability of using the composite as a thermal insulator. The analyses carried out were based on standards ABNT, ASTM and UL. The maximum temperature obtained for the composite as a thermal insulator was 200ºC, which meets the range of applications that could be used as a thermal insulator in domestic as well as industrial purposes. The experimental results prove that the composite can be used as a thermal insulator on heated or cooled surface